2019
DOI: 10.1038/s41467-019-09956-7
|View full text |Cite
|
Sign up to set email alerts
|

Observation of an oxonium ion intermediate in ethanol dehydration to ethene on zeolite

Abstract: Zeolite-catalyzed dehydration of ethanol offers promising perspectives for the sustainable production of ethene. Complex parallel-consecutive pathways are proposed to be involved in the reaction network of ethanol dehydration on zeolites, where the initial step of ethanol dehydration is still unclear particularly for the favorable production of ethene at lower temperature. Here we report the observation of a triethyloxonium ion (TEO) in the dehydration of ethanol on zeolite H-ZSM-5 by using ex situ and in situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 43 publications
3
43
0
Order By: Relevance
“…40,[45][46][47][48] To understand the reaction mechanism involving micro-porous zeolite catalysts, fully 13 C-enriched reactants have typically been used to deal with the natural abundance issue of the hetero-nuclei, including in MTH catalysis. 2,3,15,[21][22][23][24][26][27][28][49][50][51][52][53] Although very informative, this approach primarily involves the use of non-ideal reactors (e.g., mostly in situ reaction cells with a very high 'dead volume'), as well as shorter reaction times (cf. <60 min), which do not necessarily reect the real reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…40,[45][46][47][48] To understand the reaction mechanism involving micro-porous zeolite catalysts, fully 13 C-enriched reactants have typically been used to deal with the natural abundance issue of the hetero-nuclei, including in MTH catalysis. 2,3,15,[21][22][23][24][26][27][28][49][50][51][52][53] Although very informative, this approach primarily involves the use of non-ideal reactors (e.g., mostly in situ reaction cells with a very high 'dead volume'), as well as shorter reaction times (cf. <60 min), which do not necessarily reect the real reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…No ketones or aldehydes having signals in the range of 200–220 ppm were detected . The signals at 58.5 and 15 ppm were assigned to methylene and methyl groups in ethanol, respectively, indicating the existence of adsorbed ethanol . On H‐form zeolites, the formation of ethoxy species at BAS and terminal ethoxy species and/or strongly bonded ethanol are probed with signals at 72.6 and 61.7 ppm, respectively .…”
Section: Resultsmentioning
confidence: 64%
“…At the steady‐state period, both direct and indirect ethanol dehydration mechanisms are proposed for EFAl species (LAS), as those proposed for BAS (Supporting Information, Scheme S1), but exhibit a lower activity than reported BAS . In this work, we show that introducing three‐coordinate Al 3+ species could achieve the high ethanol conversion and ethylene selectivity and reach the steady‐state period in a short term.…”
Section: Resultsmentioning
confidence: 99%
“…[18,[23][24][25][26][27] Recently, more evidence was reported from experimental study as the oxonium ion was observed during the ethanol dehydration reaction. [28] Zeolites isomorphously substituted with several metals have been examined to obtain guideline for designing new enhanced catalysts. Isomorphous substitutions of B, Fe, Ga and Al into the ZSM-5 zeolite framework were studied by Fourier transform infrared spectroscopy and temperature-programmed ammonia desorption techniques.…”
Section: Introductionmentioning
confidence: 99%